Intention to Leave Among Quality Nurses in Public Hospitals in Kuwait: A Sequential Explanatory Mixed-Methods Study - Talal ALFadhalah; Shaimaa Ali; Marjan Lari; Hamad Al Kharji; Hossam Elamir (Healthcare, 2026)
Background/Objectives: In Kuwait, a marked decline in the number of quality nurses has been observed; however, the factors underpinning their intention to leave have never been investigated. This study aimed to determine the prevalence of turnover intention among quality nurses in Kuwait, describe the reported reasons for leaving, and explore the organizational and personal experiences underlying their intentions. Methods: A sequential explanatory mixed-methods design was used. The quantitative phase involved a total population survey of all eligible quality nurses working in public hospitals (n = 65), using a structured questionnaire that included demographic characteristics, the Turnover Intention Scale (TIS-6), and literature-informed reasons for leaving. Descriptive analyses and non-parametric group comparisons (Mann–Whitney U and Kruskal–Wallis H tests) were conducted. The qualitative phase comprised in-depth semi-structured interviews with seven nurses who voluntarily reported an intention to leave and agreed to explain and contextualize the quantitative findings. Interview data were analysed using inductive thematic analysis informed by phenomenological principles. Results: The mean turnover-intention score was 21.7 (SD = 3.9), exceeding the TIS-6 scale midpoint of 18. Overall, 54 of 65 participants (83.1%; 95% CI: 72.2–90.3%) scored above the TIS-6 midpoint of 18, consistent with the original developer’s scoring guidance for a desire to leave. The most frequently reported reasons for leaving were low salary (60.0%), stressful or unsupportive work environments (49.2%), and lack of recognition (44.6%). The qualitative findings expanded these results by illustrating how organizational factors were manifested in practice through poor communication, lack of managerial support, role ambiguity, blame culture, verbal mistreatment, emotional exhaustion, and perceived inequity. Three overarching themes were identified: organizational and workplace factors, compensation and benefits, and personal reasons. Predictable morning duty also emerged as a factor that participants perceived as supporting their willingness to remain in their roles. Conclusions: Turnover intention among quality nurses in Kuwait was reported primarily in relation to organizational and work-related factors rather than demographic characteristics. The qualitative findings contextualized the high turnover-intention scores by illustrating participants’ workplace experiences. These findings suggest that strengthening organizational support, clarifying professional roles, promoting equitable management practices, and reviewing remuneration structures might contribute to improving retention among quality nurses.